BTK inhibition is a potent approach to block IgE‐mediated histamine release in human basophils. Issue 11 (20th April 2017) - Smiljkovic, D.; Blatt, K.; Stefanzl, G.; Dorofeeva, Y.; Skrabs, C.; Focke‐Tejkl, M.; Sperr, W. R.; Jaeger, U.; Valenta, R.; Valent, P.
Abstract: Background: Recent data suggest that Bruton's tyrosine kinase (BTK) is an emerging therapeutic target in IgE receptor (IgER)‐cross‐linked basophils. Methods: We examined the effects of four BTK inhibitors (ibrutinib, dasatinib, AVL‐292, and CNX‐774) on IgE‐dependent activation and histamine release in blood basophils obtained from allergic patients (n=11) and nonallergic donors (n=5). In addition, we examined the effects of these drugs on the growth of the human basophil cell line KU812 and the human mast cell line HMC‐1. Results: All four BTK blockers were found to inhibit anti‐IgE‐induced histamine release from basophils in nonallergic subjects and allergen‐induced histamine liberation from basophils in allergic donors. Drug effects on allergen‐induced histamine release were dose dependent, with IC50 values ranging between 0.001 and 0.5 μmol/L, and the following rank order of potency: ibrutinib>AVL‐292>dasatinib>CNX‐774. The basophil‐targeting effect of ibrutinib was confirmed by demonstrating that IgE‐dependent histamine release in ex vivo blood basophils is largely suppressed in a leukemia patient treated with ibrutinib. Dasatinib and ibrutinib were also found to counteract anti‐IgE‐induced and allergen‐induced upregulation of CD13, CD63, CD164, and CD203c on basophils, whereas AVL‐292 and CNX‐774 showed no significant effects. Whereas dasatinib and CNX‐774 were found to inhibit the growth of HMC‐1 cells and KU812 cells, no substantial effects were seen with ibrutinib or AVL‐292. Conclusions: BTK‐targeting drugs are potent inhibitors of IgE‐dependent histamine release in human basophils. The clinical value of BTK inhibition in the context of allergic diseases remains to be determined.